Evaluation of Fitness and Learning Outcomes of Elementary School Teacher Education Students in Sports Lessons Command Model: A Literature Review - Alfroki Martha; Alfiyandri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
For students of the Primary School Teacher Education Study Program, Physical Education, Sports and Health Learning is very important in maintaining physical health as well as completing learning goals. The command-learning paradigm that accentuates the teacher has total dominance in the learning process is believed to be suitable for this circumstance. This study is conducted to evaluate the effectiveness of command learning paradigm on students’ learning results and excellent physical fitness in Sports lessons courses. This method of research analyses dedicated literative review by going through different related studies published in national as well as international journals. The article analyzed in the review is within the themes of command learning model, physical fitness and learning outcomes in Sports lessons learning. The data were analyzed in a descriptive way to identify possible relationships between the variables studied. The experimental results presented prove the beneficial effects of the command learning model on students’ physical fitness, which are mainly embodied in cardiovascular endurance, muscle strength and flexibility. Furthermore, student learning outcomes also increase effectively, especially in mastering material concept and Sports lessons motor skills. Next, the model is followed by an enormous amount of variable, such as quality and availability of teachers, learner conditions and social environment. This study concludes the command learning model is good or effective to enhance the physical fitness and learning outcomes of Elementary School Teacher Education students in Physical Education subjects. But teachers also have to be mindful of coming up with ways to keep interest and motivation in the long term. Formulation of an adaptive, individualized learning model requires additional research.